Flux Science Without Borders: Strengthening Ecosystem Flux Capacity in Latin America - Tonantzin Tarin; M. Susana Alvarado‐Barrientos; Eugenia González del Castillo; Mónica Cervantes‐Jiménez; Zulia Sánchez‐Mejía; Alejandro Cueva; Alejandro Delgado‐Guerrero; Dulce Flores‐Renteria; Jaime Garatuza‐Payan; César Hinojo‐Hinojo; Karem Meza; David J. P. Moore; et al. (Global Change Biology, 2026)
The future of how we understand and manage ecosystems largely depends on direct and continuous observations that connect local territories to planetary processes. Latin America (LATAM: Mexico, Central and South America, and the Caribbean) hosts ecosystems critical for regulating global carbon, water, and energy cycles. However, persistent underinvestment in science and technology hampers the long‐term monitoring capacity needed to advance regional priorities. Addressing the climate crisis requires investing in local researchers, technicians, and students, providing Earth System Science training that integrates biophysical and sociocultural knowledge. Although English is the lingua franca of science, training in native languages accelerates technical capacity, strengthens regional collaboration, and grounds solutions in local experience. Here, we present TAFE ( Taller de Aprendizaje de Flujos Ecosistémicos ) as an example of how regionally grounded, native‐languages training can strengthen ecosystem flux science in LATAM and beyond. Such initiatives help decentralize knowledge, reduce the underrepresentation of Global South ecosystems in flux databases, and empower the next generation to lead research for both regional and global benefit.